Invasive meningococcal disease in children in Ireland, 2001–2011. Issue 12 (26th August 2016) - Ó Maoldomhnaigh, Cilian; Drew, Richard J; Gavin, Patrick; Cafferkey, Mary; Butler, Karina M
Abstract : Background: In 1999, invasive meningococcal disease was hyperendemic in Ireland at 14.75/100 000 population, with 60% group B and 30% group C diseases. National sepsis guidelines and meningococcal C vaccines were introduced in 2000. Despite a spontaneous decline in group B infection, invasive meningococcal disease remains a leading cause of sepsis. This study characterises the epidemiology of invasive meningococcal disease in children in Ireland since the introduction of meningococcal C vaccine and reviews its clinical presentation, hospital course and outcome in anticipation of meningococcal B vaccine introduction. Methods: National surveillance data were obtained from the Health Protection Surveillance Centre. A retrospective study of all meningococcal cases at two tertiary paediatric hospitals was conducted from 2001 to 2011. Records were reviewed using a standardised assessment tool. A study of 407 meningococcal cases published in 2002 provided comparative data. Results: Of 1820 cases <19 years of age notified nationally, 382 (21%) cases attended a study hospital; 94% group B, 3% group C, 225 (59%) male, median age 5 years (range 0.1–18). Fever was absent at presentation in 18%. Fifteen patients (3.6%) died. 221 (61%) were admitted to paediatric intensive care units (PICU). Permanent sequelae occurred in 9.4%. Compared with the historical cohort, there were differences in presentation, an increase in PICU interventions, but no significant decline in morbidity or mortality. Conclusions: Despite the meningococcal C vaccination campaign, invasive meningococcal disease continues to cause serious morbidity and claim lives. Group B infections remain dominant. As children who die often present with fulminant disease, preventive strategies including use of meningococcal B vaccine are needed to avert death and sequelae.